Higher education and pandemic: a pilot study of educational experience during a pandemic questionnaire - Moreno-Candil, David (2021)
Introduction. The COVID-19 pandemic led most countries to suspend face-to-face educational activities. In Mexico, it was determined to continue the school year through distance learning. Due to the atypical nature of the situation, there are no tools to evaluate the student’s experience with this measure. Objective. Design and evaluate the psychometric properties of the Pandemic Educational Experience Questionnaire (CEEP). Method. The CEEP consists of 89 items on a Likert scale, it was applied to a non-probabilistic sample of 1,441 Mexican students of higher education. Results. An Exploratory Factor Analysis was carried out, items with a factor load lower than 0.40 were eliminated, the remaining items were grouped into 9 factors (50.836% of the total variance). The factors and the questionnaire in general yielded acceptable internal consistency values (0.670 > a > 0.991). Discussion. The CEEP is considered an adequate tool to evaluate the student experience during the pandemic. Results showed that students valued positively their aptitudes for distance learning (EaD), as well as the quality and behavior of their teachers; despite this, they report less satisfaction with the dynamics of the EaD and a negative emotional experience.